Public management in turbulent times: COVID‐19 as an ecosystem disruptor. Issue 4 (22nd November 2021) - Eriksson, Erik; Gadolin, Christian; Lindahl, Göran; Alexandersson, Patrik; Eriksson, Johanna
Abstract: The decentralisation of Swedish healthcare closer to citizens has been slow. Drawing from empirical material of the reform prior and amidst the COVID‐19 pandemic, this paper argues that the pandemic has disrupted the healthcare ecosystem. Consequently, citizen‐centred collaborations have accelerated integration of resources (such as knowledge and skills) across organisational, hierarchical and professional borders. However, collaborations have been delimited to traditional healthcare providers, neglecting the resources of citizens and other actors to be used to improve service delivery. The pandemic has revealed strengths and weaknesses with the prevailing healthcare ecosystem that post‐COVID‐19 public management must address, both theoretically and practically. Theoretically, the paper contributes to the development of a public service logic, addressing both strengths and difficulties with the logic in turbulent times. Practically, the empirical descriptions contribute to improved understanding of public service delivery reform and how it is impacted during the pandemic. Abstract : Turbulent times, such as the COVID‐19 pandemic, may accelerate reforms in a desired direction. However, expected enablers for value co‐creation in public service ecosystems, such as information technology, may be underused, despite the sense of urgency.